2020
DOI: 10.1111/jce.14454
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of convergent atrial fibrillation ablation with continuous rhythm monitoring

Abstract: Background: Outcomes of catheter ablation for persistent atrial fibrillation (PeAF) are suboptimal. The convergent procedure (CP) may offer improved efficacy by combining endocardial and epicardial ablation. Methods:We reviewed 113 consecutive patients undergoing the CP at our institution. The cohort was divided into two groups based on the presence (n = 92) or absence (n = 21) of continuous rhythm monitoring (CM) following the CP. Outcomes were reported in two ways. First, using a conventional definition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Further, since there is recovery of electrical conduction following epicardial ablation, it remains important to undertake both components of the hybrid technique to achieve long-lasting, widespread transmurality [ 63 ]. Observational clinical outcomes from contemporary analyses have suggested favourable outcomes with this technique [ 64 , 65 , 66 , 67 , 68 ], which were recently corroborated by the results of the multi-centre, randomised controlled CONVERGE trial [ 69 ]. The trial compared hybrid Convergent ablation with endocardial catheter ablation in PersAF and LSPersAF and met its primary safety and effectiveness endpoints.…”
Section: The Posterior Wall Of the Left Atrium In Non-paroxysmal Atrial Fibrillationmentioning
confidence: 88%
“…Further, since there is recovery of electrical conduction following epicardial ablation, it remains important to undertake both components of the hybrid technique to achieve long-lasting, widespread transmurality [ 63 ]. Observational clinical outcomes from contemporary analyses have suggested favourable outcomes with this technique [ 64 , 65 , 66 , 67 , 68 ], which were recently corroborated by the results of the multi-centre, randomised controlled CONVERGE trial [ 69 ]. The trial compared hybrid Convergent ablation with endocardial catheter ablation in PersAF and LSPersAF and met its primary safety and effectiveness endpoints.…”
Section: The Posterior Wall Of the Left Atrium In Non-paroxysmal Atrial Fibrillationmentioning
confidence: 88%
“…[3][4][5] Epicardial attempts at minimally invasive ablation, particularly subxiphoid or transdiaphragmatic is often incomplete, does not address the LAA, and may expose to a unique increased set of complications. [6][7][8] Robotic-assisted biatrial surgical ablation can be safely performed as a standalone or concomitant procedure and offers the ability to perform the full Cox-maze III/IV as well as direct LAA obliteration. 9,17 The safety profile and outcomes of robotic surgical ablation may mimic those obtained with sternotomy Cox-maze operations while providing a single-stage, single-incision, minimally invasive procedure to rival alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Furthermore, recent epicardial minimally invasive surgical ablation techniques, particularly subxiphoid, are arrhythmically and antomically incomplete and have potential major safety concerns. [6][7][8] Despite the known effectiveness of the cut-and-sew Coxmaze III, there exists a reluctance on the part of patients, referring cardiologists, and surgeons to carry out a sternotomy for a stand-alone cut-and-sew surgical Cox-maze. Fortunately, the electrophysiologic principles of the Coxmaze III biatrial lesions can be identically and transmurally replicated with alternate power sources consisting of bipolar radiofrequency and/or cryothermia, as the Cox-maze IV procedure (Figure 1).…”
mentioning
confidence: 99%
“…Per the Society of Thoracic Surgeons clinical practice guidelines, surgical ablation for AF is a class I recommendation when performed at the time of concomitant cardiac surgery, such as coronary artery bypass or valve surgery, and several reports document improved survival compared to patients undergoing concomitant surgery without AF treatment 80–85 . Stand‐alone surgical AF ablation continues to have a role in patients who have symptomatic AF that is refractory to AAD and catheter ablation (class IIA, LOE B), especially as a “hybrid” procedure 80,86,87 . Prior data have shown that larger LA size and longer duration of preoperative AF, both of which are linked to more advanced ACM, are predictors of persistent AF after surgical maze procedure 88–90 .…”
Section: Acm Catheter Ablation and Af Ablation Surgerymentioning
confidence: 99%
“…[80][81][82][83][84][85] Stand-alone surgical AF ablation continues to have a role in patients who have symptomatic AF that is refractory to AAD and catheter ablation (class IIA, LOE B), especially as a "hybrid" procedure. 80,86,87 Prior data have shown that larger LA size and longer duration of preoperative AF, both of which are linked to more advanced ACM, are predictors of persistent AF after surgical maze procedure. [88][89][90] Although surgical ablation has been found to be efficacious in restoring sinus rhythm, the available data to demonstrate a link between LA reverse remodeling parameters and longterm freedom from recurrent AF in those who underwent surgical ablation are overall limited.…”
Section: Acm Catheter Ablation and Af Ablation Surgerymentioning
confidence: 99%